POLICY EVALUATION AND THE ROLE OF NARCOTICS REHABILITATION INSTITUTION S IN NORTH SULAWESI - Joke Punuhsingon; Pinta Simamora; Kristiane Paendong; Joni Kutu' Kampilong; Arie Andes; Rohyani Sumilat; Christie Gumansing; Janesandre Palilingan (SOSIOEDUKASI, 2025)
This study examines how narcotic rehabilitation policies were implemented and how effective they were in North Sulawesi, Indonesia, at a time when the number of drug users increased nationally and regionally. Using a 12 month longitudinal quasi-experimental design, this study followed 400 persons with a history of narcotics use in 15 different districts. Primary and secondary data were combined in an ETL pipeline and using path analysis and structural equation modeling to investigate the relationship between policy harmonization, integration of local cultural values, community support, and relapse outcome. The results suggest that national and regional policies, if properly aligned, along with some culture-related practices, have a strong impact on strengthening formal and informal support mechanisms by and for communities. As a result, this reduced the rate of relapse by approximately 15%, as well as social reintegration indicators. Community-based involvement and the cultural practices of the community were shown to foster program legitimacy, adherence, and sustainability. The research concludes that effective narcolept rehabilitation must include not only institutional coordination and real-time data monitoring but also can only be realized through systematic valuation of local values and local community networks. These results provide evidence-based recommendations for strengthening rehabilitation governance in North Sulawesi and show the possibility of using this as a scalable model for the context-sensitive implementation of a narcotics policy that propels the country's development and is matched to its national priorities and Sustainable Development Goals.